Diseño de un plan de mantenimiento preventivo basado en confiabilidad de maquinaria amarilla encargada de la construcción del tercer carril Bogotá-Girardot del consorcio ruta 40 (2024)
The ruta 40 consortium has a wide variety of construction equipment, which is used for the extraction of material and adaptation of the land for the expansion of the 3rd lane Bogotá - Girardot. This equipment was acquired by the ruta 40 consortium at the end of the year. 2021to the Hyundai brand dealer, with which the company seeks to optimize processes and have specialized teams for each task so that field activities do not slow down. The most representative brand in the fleet of the ruta 40 consortium is the Hyundai Construction Equipment (HCE) equipment since most of these are new and this brand stands out for its research and innovation for excavator-type equipment in order to provide the highest performance and precision, as well as safety and quality for its customers.